The Factors That Influence Social Science Student Achievement of Class VII of State Junior High School in Subdistrict Tampan Pekanbaru - Mard, Hosnilawati; Sumarno, Sumarno; Gimin, Gimin (Program Pascasarjana, Universitas Riau, 2019)
This study aims to analyze the factors that influence student learning achievement. The population of this study is students of class VII State Junior High School in the Sub district of Tampan, Pekanbaru City as many as 1,091. Sampling using Proportional Random Sampling to obtain 296 students. Data collection using questionnaires and documents with a Likert scale both for exogenous variables namely learning achievement and for endogenous variables namely self-concept, learning facilities, and discipline of learning, as well as intervening variables that are motivational learning. The data analysis technique used is path analysis. The analysis showed that self-concept, learning facilities, learning discipline had direct and significant influence on learning motivation. Self concept, learning facility, learning discipline and learning motivation have direct and significant effect on learning achievement. Self concept, learning facility, learning discipline have indirect effect on learning achievement through learning motivation. This shows that learning achievement can be improved if the quality of self-concept, learning discipline, learning facilities and learning motivation are improved.